Sacralization of Peace by the Choice of Dates for Conclusion of International Treaties within Westphalian System - L. I. Ivonina (Vestnik MGIMO-Universiteta)
The issues of peace have always been important for historical science. However, in recent years, international historiography began to pay attention to Peace congresses' symbolism and socio-cultural design. The symbolic power of "special days" whether it is a Christian holiday or an event of exceptional significance allowed people of early Modernity to express their attitude to reality and power. An analysis of the choice of the dates for the conclusion of Peace by adversary states within the Westphalian system demonstrates three persistent variants of the dates. The first is signing a peace treaty on Saturday, Sunday, or a Christian holiday. The most striking example of this option is the signing of the Peace of Westphalia itself (treaties in Münster and Osnabrück on October 24, 1648), on Saturday the day before the second Sunday after Trinity. The second option involves a reference to an important event in the past. For example, the Peace in Passarovitz between the Holy Roman Empire and Porta (1718) and the Russian-Turkish Peace in Kuchuk-Kaynardzhi (1774) were signed on the same date July 21, the date when Istanbul and Peter the Great signed the Prut Peace Treaty in 1711. Since the age of the Enlightenment, when the "Right of Peace" began to compete with the "Right of War" in political theories, the date of Peace could be directly determined by the end of negotiations. Sometimes the conclusion of the Peace became a Christian holiday. Peter the Great decided to consecrate the day of the conclusion of the Nystad Peace Treaty by transferring the relics of the Holy Grand Duke Alexander Nevsky from Vladimir to the new Russian capital St. Petersburg. Conclusion of the Peace was used as a tool of social constructivism, implemented through modeling. The political idea was symbolically grounded in significant historical or religious dates. Combining the historical precedent, the Christian holiday and the end of the war emphasized the sacred nature of Peace as the highest social value.